Are Health e-Mavens the New Patient Influencers? - Díaz-Martín, Ana M.; Schmitz, Anne; Yagüe Guillén, María Jesús (Frontiers in Psychology, 2020)
Even though the healthcare industry is usually considered a rather traditional and slowly evolving sector, change is happening. Digitalization is transforming the way of obtaining medical advice and treatment and the Internet has become a key source for the seeking of healthcare information. It has allowed people to turn into more active collaborators in matters of their own health by enabling them to easily search and share information with other patients. Although research points out the growing importance of user-generated content in many sectors and its positive impact on information credibility, trust, engagement and, ultimately, customer behavior (Malthouse et al., 2016), there is a lack of attention to this topic in healthcare. In this brief review, we address this gap by analyzing the role of health e-mavens, which are a particular type of influencers that posses both expertise and social influence online, and illustrating possible benefits of their impact on others, to the parties involved in this phenomenon.